Effect of Media Types on the Growth of Callus Culture in Kumis Kucing Orthosiphon aristatus (Blume) Miq. - Wahyu Widayat; Muhammad Satyo Pradana; Mirhansyah Ardana (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2020)
The lack of conventional availability of plant Kumis Kucing makes tissue culture techniques used as a solution to overcome this problem. In tissue culture, media is a major factor in producing a good crop of plantlets. Media Murashige & Skoog (MS), Lloyd & McCown Woody Plant (WPM) media was used in the induction of Orthosiphon aristatus (Blume) Miq cat whiskers callus culture, in this study also used growth regulators in the form of 2,4-D added to each-individual media. The results showed the best callus growth occurred in Murashige & Skoog (MS) media compared to the Lloyd & McCown Woody Plant (WPM) media, where the callus produced was 3.28 g on MS media.